'I waited 12 months': how does a lack of access to housing undermine Housing First?. Issue 1 (2nd January 2019) - Bullen, Jane; Baldry, Eileen
Abstract: Housing First is recognised internationally as effective in addressing homelessness, in particular for vulnerable cohorts, yet has been implemented internationally on only a limited basis. One reason is a lack of affordable housing. This policy review investigates how an affordable housing deficit impacts on the implementation of Housing First. The review synthesises existing literature and draws upon a case study of an inner-city Housing First initiative in Sydney, Australia. The review finds that a lack of access to housing has impacted on Australian Housing First programmes, delaying access to housing in contradiction to intended goals, reducing the assistance received and reshaping programme operation. To avoid these counterproductive effects on Housing First projects and facilitate expansion of the model, governments need to take steps to make housing available. This could be achieved by providing rental vouchers, more effectively prioritising access to social housing for the most vulnerable and contracting more affordable housing.